VD_FINDINFO Jug / 2017 / 280 vom 13. Oktober 2016 - VD Tribunal cantonal (2016)
OMISSION DE PRÊTER SECOURS, NÉGLIGENCE, LÉSION CORPORELLE PAR NÉGLIGENCE, CHIEN, DILIGENCE | 56 CO, 12 al. 3 CP, 125 al. 1 CP, 128 CP